O processo de degradação e revitalização dos espaços públicos: usos e apropriações das praças no Centro Histórico de João Pessoa-PB - Teixeira, Marina da Silva (2014)
This research analyzes the transformations of the public spaces located on the historic center of João Pessoa through its uses, considering the relations of domination and appropriation that occur between the agents that act in those places. The focus is on three squares: Praça Vidal de Negreiros, also known as Ponto de Cem Réis, Praça Anthenor Navarro and Praça Rio Branco. We make a historical approach of some interventions promoted by the government and private initiatives, lighting the changes that took place on those squares and surroundings. The content and the implementation of the projects of revitalization are analyzed, identifying the impacts that they caused on the uses of those public spaces, observing some spatial practices of different people and groups in the everyday life. This work is divided in three pieces. In the first chapter is the theoretical and methodological discussion that underlies the research, bringing the approach of production and reproduction of urban space to think the transformations of public spaces located on urban centers. Besides, we present the methodological strategies and the empirical objects of analysis: the squares we chose to be the focus of this work. In the second chapter, the concepts of center and centrality are brought to clarify the process that defined the principal center and the historic center of João Pessoa. We tried to characterize the principal center of the city, highlighting its dynamic and history. We also tried to understand the significations of its degradation and revitalization among the production of urban space. Therefore, experiences of revitalization that took place in other countries and Brazilian cities are discussed, showing the recent valorization of memory and heritage of old urban areas. Finally, we recognize the (re)invention of the historic center of João Pessoa because of the projects of revitalization that occurred from the 1980 s until nowadays. In the third chapter, we reflect on the "cultural use" of public spaces and some experiences observed on the center of João Pessoa. We make a brief discussion on the construction of the concept of culture in the social sciences and how we got to the notions of culture industry and mass culture. We relate this discussion to the notions of spectacle and gentrification in urban centers, especially regarding the merchandise of places. With the contribution of Henri Lefebvre, we make a dialectical approach of the "leisure spaces" and parties. From situations experienced in field, interviews and documentary research, we analyze the project "Sabadinho Bom" ( Good Saturday ) and Beco cultural ("Cultural Alley"), two cultural projects that are taking place in Praça Rio Branco. Finally, we discuss the realization of events in other areas of the historic center, as parties and the project called "Circuito Cultural ( Cultural Tour").